Probing the origin of photoluminescence brightening in graphene nanoribbons. (9th April 2019) - Alavi, Seyed Khalil; Senkovskiy, Boris V; Pfeiffer, Markus; Haberer, Danny; Fischer, Felix R; Grüneis, Alexander; Lindfors, Klas
Abstract: We measure the absolute absorbance of a single layer of seven atom wide armchair graphene nanoribbons and study the influence of laser-induced defects on the absorption spectrum of the ribbons. We find that the absorption spectrum shows a broad peak at approximately 2.4 eV that is attributed to excitonic transitions and a smaller peak at 1.77 eV. The low-energy peak is diminished when we induce defects in the material. Simultaneously the photoluminescence is significantly enhanced. We thus attribute the 1.77 eV spectral feature in the absorption spectrum to a quenching state, which energetically coincides with the emission. Our results clearly demonstrate the significance of this state in photoluminescence processes in the ribbons. We additionally measure the dependence of the generation of defects on the energy of the incident photons and the photoluminescence excitation spectrum. The photoluminescence excitation efficiency peaks at a higher photon energy than the maximum absorption, hinting at an efficient decay from higher energetic states to the emissive state.